PERFORMANCE AND KINETICS OF AN INTEGRATED SUSPENDED AND SUBMERGED ATTACHED GROWTH BIOREACTOR TREATING INDUSTRIAL WASTEWATER - EZECHI, EZERIE HENRY (2016)
Biological wastewater treatment technology is an aged long ctTective method associated with numerous advantages in tem1s of operational cost. However, conventional biological wastewater treatment technologies are also associated with demerits such as large space requirement due to the segregated compartments. Efforts to overcome this demerit have been intensified through the integration of various bioreactor compartments into a single entity as well as the immobilization of microorganisms on submerged media. In this study, the performance of an identical laboratory scale integrated suspended growth bioreactor (ISGB) and an integrated submerged attached growth bioreactor (ISAGB) was evaluated for the treatment of wastewater. The bioreactor has a total working volume of 180 L (aerobic 10 L; anoxic 20 L and settling unit 150L).